Synthesis, characterization, density functional theory, X‐ray study, thermal stability, and biological and MOE relevance of metal complexes of griseofulvin. (8th March 2018) - Mahmoud, Walaa H.; Mahmoud, Nessma F.; Mohamed, Gehad G.
Abstract : Metal(II) and metal(III) coordination compounds of griseofulvin (GFV) drug were synthesized. The structure of the ligand was determined on the basis of elemental analyses, infrared and 1 H NMR spectroscopies and thermal studies. GFV behaved as a neutral tridentate chelating agent and coordinated to metal ions through three oxygen atoms: two methoxy groups and oxygen atom of furan ring. Metal complexes were characterized by means of elemental analyses and molar conductance, spectral (infrared, electron spin resonance) and thermal studies. All the complexes showed molar conductance behaviour corresponding to an electrolytic nature. All the complexes showed octahedral geometry, except [Zn(GFV)Cl]Cl that showed tetrahedral geometry. Density functional theory (DFT) calculations were employed to understand and estimate the contribution of each interaction in the formation of the assembly using several theoretical models. The computed parameters from DFT calculations for structure optimizations and vibrational frequencies were in good agreement with the experimental data. Newly synthesized metal complexes in addition to GFV were examined against opportunistic pathogens. The biological applications of complexes were studied with two Gram‐positive bacteria ( Bacillus subtilis and Staphylococcus aureus ) and two Gram‐negative bacteria ( Escherichia coli and Neisseria gonorrhoeae ) as well as their antifungal activity against Candida albicans . Results suggested that metal complexes were more biologically sensitive than free ligand. The complexes showed a moderate inhibition of MCF7 breast cancer cell line growth. Molecular docking studies further helped in understanding the mode of action of the compounds through their various interactions with the crystal structures of: human serum albumin (PDB: 5FUO), Staphylococcus aureus nucleoside (PDB: 3Q8U), human acetylcholinesterase (PDB: 1B41) and the human DNA–Topo I complex (PDB: 1SC7). Abstract : Griseofulvin drug, GFV and its six new transition metal complexes were prepared and characterized using different tools. Molecular docking studies with receptors of different proteins showed highest binding ability and the minimum binding energy. The results of biological activity assay of ligand and the complexes suggested the Zn(II) complex exhibited the highest antibacterial activity.